Hubungan Bimbingan Orang Tua dengan Keterampilan Membaca Permulaan Siswa Kelas II SD Negeri Rawamangun 01 Pagi Jakarta Timur - Bugi Kurnia Dewi; Petrus Paulus Mbette Suhendro; Waluyo Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between parental guidance and the beginning reading skills of grade II students of SD Negeri Rawamangun 01 Pagi East Jakarta. This study used a quantitative approach with a correlational method. Data collection techniques were conducted through questionnaires and reading tests. The sample in this study amounted to 55 students selected by simple random sampling technique. The data were analyzed using Pearson correlation test and t-test. The results showed that there was a positive and significant relationship between the parents' guidance and early reading skills with a correlation coefficient of 0.668 and tcount of 6.268 > ttable 2.006. The relationship is classified in the strong category.